Validity and Reliability of the Reflux Symptoms Index Translated into Indonesian: The Role of Upper Endoscopy in Assessing Extra-Esophageal Gastroesophageal Reflux Disease Symptoms - Titong Sugihartono; Amal Arifi Hidayat; Michael Austin Pradipta Lusida; Kuntaman; Hafeza Aftab; Muhammad Miftahussurur (The Korean Journal of Gastroenterology, 2023)
Background/Aims: The Reflux Symptom Index (RSI) is a questionnaire that evaluates the severity of extra-esophageal symptoms and is one of the most widely used measures to evaluate LPR. This study assessed the validity and reliability of the RSI questionnaire in Bahasa Indonesia and investigated the association between each extra-esophageal symptom reported in the questionnaire and the severity of erosive esophagitis as determined by endoscopic findings. Methods: 85 adult patients with GERD symptoms had an upper endoscopy examination and were asked to complete the translated RSI. The validity and reliability of the questionnaire were assessed. Results: The construct validity of the RSI translated into Bahasa Indonesia was verified with the r value of each question being higher than the crucial table value (r>0.213, p<0.05). Our questionnaire had a Cronbach alpha value of 0.81, which indicates an acceptable level of internal consistency. At least one extra-esophageal symptom was seen in 91.7% of patients with Los Angeles (LA) grade B or higher-grade esophagitis. In addition, the presence of extra-esophageal symptoms was associated with significant mucosal erosion (p=0.20). The symptoms of cough after eating or lying down and chronic cough were associated with the severity of esophageal mucosal erosion (p<0.05). Conclusions: The version of RSI translated into Bahasa Indonesia is a valid and reliable tool for assessing extra-esophageal GERD symptoms. The occurrence of extra-esophageal symptoms in patients with typical GERD symptoms is associated with endoscopic findings of LA grade B or erosive esophagitis of higher severity.